Sosialisasi dan Pelatihan Budidaya Tanaman Hortikultura di Desa Batu Jangkih, Lombok Tengah - Hamdi, Saipul; Kusuma Wijaya, Ade Setian; Anugran, Lalu Gagarin; Savita P., Ayudia Davina; Rizal, Fachrul; Komala Asri, Baiq Isma; Haliza R., Lale Audina; Wardani, Ika Auliya; Putuhena, Dwitri Pebrian; Rizkia, Dita; Ramdani, Muh. (Jurnal Ilmiah Pengabdian dan Inovasi, 2022)
The problem faced by the community of Batu Jangkih Village, Southwest Praya, in maximizing their home yard as a sustainable home yard is the lack of knowledge and training on how to cultivate horticultural crops, whether in the form of vegetables or fruits in their yards. In fact, each of the residents' home gardens has a large enough land to be used as land for plant cultivation. Moreover, food needs such as vegetables and fruit are still depend on the supply of the market which is only held once a week because of the location of Batu Jangkih Village which is located in the hills. Therefore, it is necessary to provide understanding and awareness for the villagers of Batu Jangkih on how to use the yard of the house as a land for horticultural cultivation through socialization and training in the field. The method of activities carried out is counseling, discussions and direct practical demonstrations in the field based on an initial evaluation as a basis for determining the position of knowledge of the target group regarding the use of yard land through the application of the concept of Sustainable Food House Areas. From the results of the activities that have been carried out, it can be concluded that basically the climatic conditions and soil fertility of Bat Jangkih village are very suitable for cultivation of vegetables and fruits, but the community, especially housewives in Batu Jangkih Village, have not utilized their yards. maximally because there is no awareness of it.